Comparison of pregnant women's anxiety, depression and birth satisfaction based, on their traumatic childbirth perceptions - Barut, Sumeyye; Ucar, Tuba; Yilmaz, Ayse Nur (Taylor & Francis Inc, 2022)
This study was conducted to identify and compare pregnant women's anxiety, depression, and birth satisfaction levels based on their traumatic childbirth perceptions. This study used a cross-sectional design. The data were collected at two stages, namely, the prenatal and postpartum stages. First, the Traumatic Childbirth Perception Scale, the Beck Anxiety Inventory, and the Beck Depression Inventory were applied to the pregnant women. Next, in the postpartum period, the Childbirth Information Form and the Birth Satisfaction Scale-Revised were applied. It was found that the participants with high levels of traumatic childbirth perception had higher mean anxiety and depressive symptom scores (26.13 +/- 11.30 and 16.16 +/- 9.02, respectively), whereas the participants with low levels of traumatic childbirth perception had a higher mean birth satisfaction score (17.50 +/- 4.91). The findings indicated that high levels of traumatic childbirth perception may lead to have anxiety and depression, while low levels of traumatic childbirth perception may enhance their birth satisfaction. IMPACT STATEMENT What is already known on this subject? In the literature, it is stated that the perception of a traumatic birth can lead to permanent or long-term negative consequences in women's lives, negatively affecting their future health, subsequent birth experiences, and family relationships. What do the results of this study add? In this study, 37.7% of the participants were found to have high levels of traumatic childbirth perception. It was determined that the anxiety and depression levels of the participants with high levels of perception of traumatic birth were higher, and the levels of birth satisfaction were higher in the pregnant women with low levels of perception of traumatic birth. The results indicated that severe depressive symptoms, severe anxiety, and low levels of birth satisfaction were likely to raise traumatic childbirth perception levels in pregnant women. What are the implications of these findings for clinical practice and/or further research? The care to be given under the leadership of midwifery professionals is important in terms of reducing pregnant women's perceptions of a traumatic birth, anxiety, and depression levels and increasing their levels of birth satisfaction.
Keywords: Anxiety; birth satisfaction; depression; traumatic childbirth perception; pregnant women